PENGEMBANGAN LEMBAR KERJA SISWA (LKS) MATEMATIKA BERBASIS PROBLEM SOLVING PADA SISWA KELAS III SD NEGERI 1 WIDODO - P, Windy Herdiyanti; Asep Sukenda Egok; Elya Rosalina (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to develop valid, practical, and effective Problem Solving-based Mathematics Student Worksheets (LKS) for grade III students of SD Negeri 1 Widodo. The LKS previously used at SD Negeri 1 Widodo were still monotonous (black and white text and images) and the material presented was incomplete, resulting in a lack of student enthusiasm and the Minimum Completion Criteria (KKM) of 65 not being achieved in mathematics learning. This study used the Research and Development (R&D) method with the ADDIE (Analysis, Design, Development, Implementation, Evaluation) model. The LKS design was created using the Canva application. The results of the study showed that the LKS developed had a "very valid" level of validity with an average Aiken's V score of 0.87 from the assessment of language, media, and material experts. In terms of practicality, the LKS was declared "very practical" based on teacher responses of 90% and student responses in individual trials (91.9%) and small groups(91.67%) with an overall average of 91.19%. Meanwhile, the level of effectiveness of LKS is classified as "high" with an N-Gain value of 0.73, leading to an increase in student learning outcomes from an average pre-test of 35.32 to a post-test of 82.58. Based on these results, it can be concluded that the development of LKS Mathematics based on Problem Solving is stated in the learning process for grade III students of SD Negeri 1 Widodo.